Spectrum of antibacterial activity and mode of action of a novel tris-stilbene bacteriostatic compound - Man, Nikki Y. T. (Sci Rep, 2018)
The spectrum of activity and mode of action of a novel antibacterial agent, 135C, was investigated using a range of microbiological and genomic approaches. Compound 135C was active against Gram-positive bacteria with MICs for Staphylococcus aureus ranging from 0.12–0.5 μg/ml. It was largely inactive against Gram-negative bacteria. The compound showed bacteriostatic activity in time-kill studies and did not elicit bacterial cell leakage or cell lysis. Checkerboard assays showed no synergy or antagonism when 135C was combined with a range of other antibacterials. Multi-step serial passage of four S. aureus isolates with increasing concentrations of 135C showed that resistance developed rapidly and was stable after drug-free passages. Minor differences in the fitness of 135C-resistant strains and parent wildtypes were evident by growth curves, but 135C-resistant strains did not show cross-resistance to other antibacterial agents. Genomic comparison of resistant and wildtype parent strains showed changes in genes encoding cell wall teichoic acids. 135C shows promising activity against Gram-positive bacteria but is currently limited by the rapid resistance development. Further studies are required to investigate the effects on cell wall teichoic acids and to determine whether the issue of resistance development can be overcome.